Cardioprotection by cardiac progenitor cell-secreted exosomes: role of pregnancy-associated plasma protein-A. Issue 7 (5th March 2018) - Barile, Lucio; Cervio, Elisabetta; Lionetti, Vincenzo; Milano, Giuseppina; Ciullo, Alessandra; Biemmi, Vanessa; Bolis, Sara; Altomare, Claudia; Matteucci, Marco; Di Silvestre, Dario; Brambilla, Francesca; Fertig, Tudor Emanuel; et al.
Abstract: Aims: Cell therapy trials using cardiac-resident progenitor cells (CPCs) and bone marrow-derived mesenchymal stem/progenitor cells (BMCs) in patients after myocardial infarction have provided encouraging results. Exosomes, nanosized extracellular vesicles of endosomal origin, figure prominently in the bioactivities of these cells. However, a head-to-head comparison of exosomes from the two cell types has not been performed yet. Methods and results: CPCs and BMCs were derived from cardiac atrial appendage specimens and sternal bone marrow, respectively, from patients ( n = 20; age, 69.9 ± 10.9) undergoing heart surgery for aortic valve disease and/or coronary artery disease. Vesicles were purified from cell conditioned media by centrifugation/filtration and ultracentrifugation. Vesicle preparations were predominantly composed of exosomes based on particle size and marker expression (CD9, CD63, CD81, Alix, and TSG-101). CPC-secreted exosomes prevented staurosporine-induced cardiomyocyte apoptosis more effectively than BMC-secreted exosomes. In vivo, CPC-secreted exosomes reduced scar size and improved ventricular function after permanent coronary occlusion in rats more efficiently than BMC-secreted exosomes. Both types of exosomes stimulated blood vessel formation. CPC-secreted exosomes, but not BMC-derived exosomes, enhanced ventricular function after ischaemia/reperfusion. Proteomics profiling identified pregnancy-associated plasma protein-A (PAPP-A) as one of the most highly enriched proteins in CPC vs. BMC exosomes. The active form of PAPP-A was detected on CPC exosome surfaces. These vesicles released insulin-like growth factor-1 (IGF-1) via proteolytic cleavage of IGF-binding protein-4 (IGFBP-4), resulting in IGF-1 receptor activation, intracellular Akt and ERK1/2 phosphorylation, decreased caspase activation, and reduced cardiomyocyte apoptosis. PAPP-A knockdown prevented CPC exosome-mediated cardioprotection both in vitro and in vivo . Conclusion: These results suggest that CPC-secreted exosomes may be more cardioprotective than BMC-secreted exosomes, and that PAPP-A–mediated IGF-1 release may explain the benefit. They illustrate a general mechanism whereby exosomes may function via an active protease on their surface, which releases a ligand in proximity to the transmembrane receptor bound by the ligand.